PENGARUH RETURN ON ASSET, LOAN TO DEPOSIT RATIO, DAN CAPITAL ADEQUACY RATIO TERHADAP HARGA SAHAM - Lucy Maya Enjela; Ickhsanto Wahyudi (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2022)
This study aims to determine the effect of Return on Assets, Loan to Deposit Ratio, and Capital Adequacy Ratio on stock prices. In this study using stock prices as the dependent variable, and with three types of independent variables, namely Return on assets, Loan to Deposit Ratio, and Capital Adequacy. The population in this study are all conventional banking sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021. The sampling technique used purposive sampling, and as many as 24 companies were selected as samples. This research model uses a causal design and multiple linear regression analysis with secondary data types. The program used in this study uses the Statistical Program for Social Science (SPSS) 25 software in processing data. From these results it can be concluded that Return on Assets, Loan to Deposit Ratio, and Capital Adequacy simultaneously affect stock prices. Partially, Return on Assets (ROA) has a positive and significant effect on stock prices, Loan to Deposit Ratio (LDR) has a significant and negative effect on stock prices, and Capital Adequacy Ratio (CAR) has no effect on stock prices. Further researcher are expected to consider other variable related to stock prices or other sector and update research period for future period.